Hypoxia-induced gene expression in murine alveolar macrophages - Israeli, Zeev; Justus Liebig University Giessen (My University, 2009)
Hypoxia is known to trigger inflammatory reaction solely or in concert with other stimuli leading to lung damage. Hypoxia- induced lung damage is mediated by the secretion of pro-inflammatory cytokines by alveolar macrophages (AM). To learn more about the genes involved in the hypoxia mediated- activation of AM, m-RNA of AM from mice kept under normoxia/hypoxia for 1 or 21 days was isolated and studied using three established techniques: Microarrays, real-time PCR and immunohistochemistry. Array results confirmed that hypoxia is a mild stimulus for macrophages; No strongly regulated genes were identified and the expression pattern of selected genes as explored by PCR did not support arrays findings. Immunostaining for two selected genes demonstrated a decrease of vimentin expression under acute hypoxia (1 day) and an increase of integrin b2 expression under chronic hypoxia (21 days).Our findings show that hypoxia is a mild stimulus in AM; identification of genes with mild regulation is difficult so future studies should rely on a considerably larger sample sizes. Regulation was confirmed on protein level by immunohistochemical staining for two selected genes, more studies are needed for validation and better understanding of this phenomena.
Keywords: Hypoxia; gene expresion; alveolar macrophages; ddc:610